Mengemas Unggah- Ungguh Jawa dan Nilai- Nilai Akhlak di Paud Berdasarkan Paradigma Charlotte Mason - Anugrahbputri, Weni Tria; Nasyiithoh, Hikma Khilda (Proceedings of Annual Conference for Muslim Scholars, 2019)
This paper aims to describe a learning of Javanese etiquette (Unggah- ungguhJawa) combined with Islamic values ​​based on a paradigm from Charlotte Mason. This study began when the author felt anxious about the number of cases of inconvenience that often occur in recent years. The focus is the increasingly eroded pure values ​​of Islam and the erosion of positive culture, which is about manners in Javanese culture. Early Childhood is the next generation of the nation. Good learning is needed so that children are able to understand what is their duty not just to carry out tasks that they often don't want to have. Based on the Charlotte Mason paradigm, a child learns from absorbing all forms of attitudes he sees from those around him. Thus, learning must accommodate that the child is a whole person, namely recognizing oneself as God Almighty creatures who are so valuable, aware of their potential, aware of things that are obligatory, aware of how to do them.